Sensemaking approach e comportamento informacional de arquivistas na gestão de documentos universitários - Santos, José Carlos Sales dos; Silva, Teotonilía Maria Batista da; Freitas, Roberto Gonçalves (Faculdade de Filosofia e Ciências, 2020)
The article aims to analyze how informational behavior of archivists interferes in the process of managing documents produced in universities, from the sensemaking approach. The methodological contributions corresponded to the monographic procedure method (case study), inscribed in the Coordination of Archives and Documentation of the Federal University of Bahia (CAD/Ufba), with descriptions of the activities of archivists, assistants and technicians in archives in the institutional environment. The research instrument checked the structuring of an electronic questionnaire, which sought to characterize the skills of archivists in the process of representation and organization of university documents, the strategies of search and retrieval of contents in formal/informal information systems and the routine of management activities, organization and service to users and supervision of archival collections. The results showed that the servers agree with the relevance of the structures of informational behavior directed to the development of archival activities, but recognize that operational and bureaucratic factors limit the organizational practices in the coordination analyzed. The final considerations point out that the sensemaking approach of archivology professionals positively interferes in the management of archival documents of Ufba, despite the scarce resources destined for the development of management activities.